Friendly visiting and partial enquiry (proof copy)
1902-02 1902 1900s 15 pages PROOF. CONFIDENTIAL. FRIENDLY VISITING AND PARTIAL ENQUIRY. The following recommendations of the Administrative Committee were adopted by the Council on March 25, 1901:— 1. That for six months, as an experiment, the Almoners at the Royal Free Hospital, the St. George's Hospital, and the Westminster Hospital be permitted to refer to District Committees any cases of out-patients or casualty patients for the verification of statements made to the Almoners by such patients, and that the District Committees verify such statements and report to the Almoners. 2. That the Almoners at the close of each three months report to the Council of the Charity Organisation Society on the working of the arrangement and on the action taken by the several hospitals on the reports made by District Committees ; and that the Almoners' reports be transmitted to the District Committees. 3. That at the close of the six months the whole question be reconsidered. 4. That the Almoner at the hospital always tell the patient whose statements she desires to have verified that she is asking the Charity Organisation Society to verify his statements ; that she do not refer to a District Committee any case in which the applicant has not consented to the inquiry being made, and that such consent be entered on the hospital case-papers ; also that the Almoner, if she desires information as to the wages of the applicant, obtain his consent to enquiry being made of the employer, and note this consent on the hospital case-papers. 5. That in each case the Almoner send the hospital case-papers to the District Committee with a note of the points which she desires to have verified. 6. That the District Committee accept the statements set down in the hospital case-papers as a sufficient preliminary to the investigation, and do not require the applicant to attend at the office to have his case taken down in the ordinary way, as if he were making an application to the Society for relief. 378/IMSW/A/1/1/9